2016
DOI: 10.3892/ol.2016.5477
|View full text |Cite
|
Sign up to set email alerts
|

Imbalanced adaptive responses associated with microsatellite instability in cholangiocarcinoma

Abstract: The adaptive response of the genome protection mechanism occurs in cells when exposed to genotoxic stress due to the overproduction of free radicals via inflammation and infection. In such circumstances, cells attempt to maintain health via several genome protection mechanisms. However, evidence is increasing that this adaptive response may have deleterious effect; a reduction of antioxidant enzymes and/or imbalance in the DNA repair system generates microsatellite instability (MSI), which has procarcinogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…The variability in the incidence of dMMR might be explained by two reasons. First, in iCCA, reports based on analysis in Southeast Asia, particularly Thailand, appear to be strongly associated with liver fluke 19,20 . In these reports, the incidence of MSI‐H were high with 20%‐69%.…”
Section: Discussionmentioning
confidence: 99%
“…The variability in the incidence of dMMR might be explained by two reasons. First, in iCCA, reports based on analysis in Southeast Asia, particularly Thailand, appear to be strongly associated with liver fluke 19,20 . In these reports, the incidence of MSI‐H were high with 20%‐69%.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was hypothesized that methylation and somatic alterations may have been associated with loss of MLH1 or MSH2 expression in the cases with dMMR/MSH-H, since these patients did not have any past history or family history of cancer. A study from Thailand ( 45 ) reported that CCA derived from liver fluke infection had a high incidence of MSI-H (9/13 cases, 69%). Although the pathogenesis of BTC in Japan is expected to be different from that in Thailand, the study will contribute to identify the mechanisms of alteration to MSI-H, leading to an increased understanding of the development of BTC.…”
Section: Discussionmentioning
confidence: 99%
“…Loilome and collaborators demonstrated, in an O. viverrini hamster cholangiocarcinoma model, that both enzymes are highly expressed during cholangiocarcinogenesis, while there is a decreased expression when tumors are well established [ 30 ]. The same group demonstrated that both proteins are expressed at different levels in CCA tissues, but they are also expressed in normal bile ducts and hepatocytes [ 31 ]. Interestingly, its activity is dramatically reduced in CCA compared to normal bile ducts.…”
Section: Discussionmentioning
confidence: 99%